A Framework to Design Appliances for the Circular Economy Scenario - Chiara Battistoni (DIID, 2024)
Should the appliances change to adapt to new conditions in the current scenario of a compromised environmental situation? The human needs to cook food, wash dishes and do laundry are the same, but society and our relationship with mother nature have changed radically. Although many contributions to the design for sustainability, the changes in the design sector and the market are not always visible. This paper is part of a research project on the design of appliances for the circular economy scenario and intends to understand Is there the need to re-design the current one, design new ones, or invent something else? How to decide? Are we considering all the aspects? The problem was tackled using a systemic design approach. The result is a framework that contains the data collected by the research steps, maps all the implications that the design of appliances in the circular economy scenario should consider in the process, and visualises the complexity of the topic.